2014
DOI: 10.3390/toxins6041308
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Growth of F. graminearum in Wheat Plants and Related Accumulation of Deoxynivalenol

Abstract: Fusarium head blight (FHB) is an important disease of wheat worldwide caused mainly by Fusarium graminearum (syn. Gibberella zeae). This fungus can be highly aggressive and can produce several mycotoxins such as deoxynivalenol (DON), a well known harmful metabolite for humans, animals, and plants. The fungus can survive overwinter on wheat residues and on the soil, and can usually attack the wheat plant at their point of flowering, being able to infect the heads and to contaminate the kernels at the maturity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 30 publications
3
37
0
Order By: Relevance
“…Differently, Covarelli et al (2012) and Winter et al (2013) reported that F. culmorum, in wheat, was unable to colonize the head most likely due to the presence of a lignin layer in the parenchymal cells of the culm. A similar phenomena was described for F. graminearum in durum wheat where the pathogen was not able to reach the head, probably because of a kind of barrier (Moretti et al 2014). …”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Differently, Covarelli et al (2012) and Winter et al (2013) reported that F. culmorum, in wheat, was unable to colonize the head most likely due to the presence of a lignin layer in the parenchymal cells of the culm. A similar phenomena was described for F. graminearum in durum wheat where the pathogen was not able to reach the head, probably because of a kind of barrier (Moretti et al 2014). …”
Section: Discussionsupporting
confidence: 67%
“…As already shown in wheat (Mudge et al 2006, Covarelli et al 2012, Winter et al 2013, Moretti et al 2014, FCR is a potential additional source of grain contamination with Fusarium mycotoxins. Thus, the objective of this study was to investigate the ability of F. graminearum, F. culmorum and F. pseudograminearum to systemically colonize barley plants starting from the stem base by visual, scanning electron microscope and Real-Time PCR methods and to verify the possible DON accumulation in the head.…”
Section: Manuscript Received December 2017mentioning
confidence: 63%
See 2 more Smart Citations
“…Fusarium culmorum might have produced DON that moved from lower parts of the plants to the heads, consistent with the results of Moretti et al . () and Covarelli et al . () who demonstrated that, although F. graminearum and F. culmorum could not be detected beyond the third internode, a low concentration of DON was found in the kernels beyond those tissues colonized by the fungus, suggesting that DON can be moved from lower parts of the plants to the heads.…”
Section: Discussionmentioning
confidence: 84%